2010
DOI: 10.1111/j.1524-4725.2010.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Surgery Is Effective for High-Risk Cutaneous Squamous Cell Carcinoma

Abstract: MMS is an effective treatment for high-risk cutaneous SCC. This represents the largest single-center study of high-risk SCC supporting the use of MMS. Adjuvant radiotherapy was reserved for large-nerve perineural disease. There was a low recurrence rate and disease-specific mortality. Prompt recognition of metastatic disease allowed for curative therapy. Patients with one high-risk SCC are likely to develop secondary primary SCC and melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 18 publications
(23 reference statements)
0
71
0
10
Order By: Relevance
“…568,572 Six studies reported recurrence in the regional lymph nodes after treatment with MMS. 545,564,565,567,569,573 On pooled analysis (comprising 1162 patients) the average regional recurrence was 4.2% (95% CI 2.3% to 6.6%; I 2 = 56%) ( Figure 37). There was no significant impact on regional recurrence in the sensitivity analysis, which included only four studies meeting the criteria, 545,565,567,569 with average recurrence of 3.2% (95% CI 1.9% to 5.0%, I 2 = 29%).…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…568,572 Six studies reported recurrence in the regional lymph nodes after treatment with MMS. 545,564,565,567,569,573 On pooled analysis (comprising 1162 patients) the average regional recurrence was 4.2% (95% CI 2.3% to 6.6%; I 2 = 56%) ( Figure 37). There was no significant impact on regional recurrence in the sensitivity analysis, which included only four studies meeting the criteria, 545,565,567,569 with average recurrence of 3.2% (95% CI 1.9% to 5.0%, I 2 = 29%).…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
“…Four studies with mean follow-up of between 2 and 5 years reported death attributable to SCC, 564,565,569,571 with an average of 1.1% (95% CI 0.2% to 2.6%; I 2 = 49%) of the 941 eligible patients dying from disease on pooled analysis (Figure 39). One of the included studies reported a relatively high proportion of deaths compared with the other studies.…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…[71][72][73] Tissue is excised and examined intraoperatively as frozen section to confirm clear margins and limit unnecessary further resection. 71,72 The systematic review of Lansbury et al 74 reports pooled estimate of local recurrence during variable follow-up periods after MMS from 10 studies was 3.0% (2.2 to 3.9%), which was nonsignificantly lower than the pooled average local recurrence of 5.4% (2.5-9.1%) after standard surgical excision (12 studies), and 6.4% (3.0-11.0%) after external radiotherapy (7 studies).…”
Section: Mohs Microsurgerymentioning
confidence: 99%